Evolution of Yrast states and B(E2 : 8₁⁺ → 6₁⁺ ) VALUES OF ¹¹⁴, ¹¹⁶, ¹¹⁸, ¹²⁰, ¹²²Cd by interacting boson model (IBM-1) - Hossain, I.; Abdullah, Hewa Y.; Ahmed, I.M.; Murarak, A.A. (Вопросы атомной науки и техники, 2015)
In this paper we address the evolution of yrast levels of low-lying structure in the neutron-rich even-even ¹¹⁴⁻¹²²Cd nuclei within the framework of interaction boson model (IBM-1). The reduced transition probabilities B(E2) ↓ between 8₁⁺ to 6₁⁺ states of even-even neutron rich Cd nuclei for N = 66; 68; 70; 72; 74 have been calculated by IBM-1 and compared with the previous available experimental values. The calculated values of ¹¹⁴, ¹¹⁶, ¹¹⁸, ¹²⁰, and ¹²²Cd, are 0.272 e²b², 0.281 e²b², 0.259 e²b², 0.190 e²b² and 0.149 e²b² respectively. The ratio of the excitation energies of the first 4⁺ and the first 2⁺ excited states, R₄/₂, were also calculated for those nuclei. The ¹¹⁴⁻¹²²Cd isotopes in U(5) - O(6) transitional symmetry were investigated. We have studied the systematic B(E2) values as a function of even neutrons from N = 66 to 74. Furthermore as a measure to quantify the evolution, we have studied systematically the ground state energy ratios RL = E(L⁺) / E(21⁺ ) and transition rate R = B(E2 : L⁺ → (L - 2)⁺) / B(E2 : 2⁺ → 0⁺) of some of the low-lying quadrupole collective states in comparison to the available experimental data.